mRNA fragments in in vitro culture media are associated with bovine preimplantation embryonic development - Kropp, Jenna (Front Genet, 2015)
In vitro production (IVP) systems have been used to bypass problems of fertilization and early embryonic development. However, embryos produced by IVP are commonly selected for implantation based on morphological assessment, which is not a strong indicator of establishment and maintenance of pregnancy. Thus, there is a need to identify additional indicators of embryonic developmental potential. Previous studies have identified microRNA expression in in vitro culture media to be indicative of embryo quality in both bovine and human embryos. Like microRNAs, mRNAs have been shown to be secreted from cells into the extracellular environment, but it is unknown whether or not these RNAs are secreted by embryos. Thus, the objective of the present study was to determine whether mRNAs are secreted into in vitro culture media and if their expression in the media is indicative of embryo quality. In vitro culture medium was generated and collected from both blastocyst and degenerate (those which fail to develop from the morula to blastocyst stage) embryos. Small-RNA sequencing revealed that many mRNA fragments were present in the culture media. A total of 17 mRNA fragments were differentially expressed between blastocyst and degenerate conditioned media. Differential expression was confirmed by quantitative real-time PCR for fragments of mRNA POSTN and VSNL-1, in four additional biological replicates of media. To better understand the mechanisms of mRNA secretion into the media, the expression of a predicted RNA binding protein of POSTN, PUM2, was knocked down using an antisense oligonucleotide gapmer. Supplementation of a PUM2 gapmer significantly reduced blastocyst development and decreased secretion of POSTN mRNA into the media. Overall, differential mRNA expression in the media was repeatable and sets the framework for future study of mRNA biomarkers in in vitro culture media to improve predictability of reproductive performance.